Micro- and Nanorobots Meet DNA - Urso, Mario; Pumera, Martin (Wiley VCH, 2022)
DNA, the well-known molecule that carries the genetic information of almost all forms of life, represents a pivotal element in formulating intelligent and versatile micro/nanorobotic systems. DNA-functionalized micro/nanorobots have opened new and exciting opportunities in many research areas due to the synergistic combination of self-propulsion at the micro/nanoscale and the high specificity and programmability of DNA interactions. Here, their designs and applications are critically reviewed, which span from the use of DNA as the fuel to chemotactically power nanorobots toward cancer cells to DNA as the main building block for sophisticated phototactic biorobots, DNA nanodevices to self-monitor microrobots' activity status, DNA and RNA sensing, nucleic acids isolation, gene therapy, and water purification. The perspective on future directions of the field is also shared, envisioning DNA-mediated reconfigurable assemblies of nanorobotic swarms.

DNA, the well-known molecule that carries the genetic information of almost all forms of life, represents a pivotal element in formulating intelligent and versatile micro/nanorobotic systems. DNA-functionalized micro/nanorobots have opened new and exciting opportunities in many research areas due to the synergistic combination of self-propulsion at the micro/nanoscale and the high specificity and programmability of DNA interactions. Here, their designs and applications are critically reviewed, which span from the use of DNA as the fuel to chemotactically power nanorobots toward cancer cells to DNA as the main building block for sophisticated phototactic biorobots, DNA nanodevices to self-monitor microrobots' activity status, DNA and RNA sensing, nucleic acids isolation, gene therapy, and water purification. The perspective on future directions of the field is also shared, envisioning DNA-mediated reconfigurable assemblies of nanorobotic swarms.
Micro- and Nanorobots Meet DNA
Keywords: aptamers; DNA; fluorescence; gene deliveries; gene silencing; micromotors; motion-based sensors; nanomotors; nucleic acids; oligonucleotides; RNA; water remediation; aptamers; DNA; fluorescence; gene deliveries; gene silencing; micromotors; motion-based sensors; nanomotors; nucleic acids; oligonucleotides; RNA; water remediation